Penerapan Model Pembelajaran Berbasis Masalah untuk Meningkatkan Kompetensi Literasi Sains Materi Kelarutan dan KSP Pada Siswa Kelas XI IPA 4 MAN 2 Kudus Semester Genap Tahun Pelajaran 2014/2015 - Indrawati, Sri (LP3 Universitas Negeri Semarang, 2015)
The outline of this research issues are how the process of, learning dhemistry use problem-based learning model, how the effectiveness of the application of the model of problem-based learning, and how to increase literacy competence of science students on Solublity and Ksp material. Subject of the research are the students of clas IX IPA 4 of Kudus MAN school year 2014/2015. The result shows that cognitive learning students improve from cycle I to cycle II, namely the number of students who pass are 43.5% and increase the percentage of classical completenass to 87.5%. The analysis results of N-gain competence in science literacy is 0.60, it’s also include in medium category and the average value about 84.2. Therefore, using this problem-based learning model can be one of the teacher’s reference to carry out a process of learning and increase literacy science students.